phytohormone crosstalk paradigm takes center stage in understanding how plants respond to abiotic stresses - Kohli, Ajay; Sreenivasulu, Nese; Lakshmanan, Prakash; Kumar, Prakash P (Plant cell reports, 2013)
The highly coordinated, dynamic nature of growth requires plants to perceive and react to various environmental signals in an interactive manner. Elaborate signaling networks mediate this plasticity in growth and the ability to adapt to changing environmental conditions. The fluctuations of stress-responsive hormones help alter the cellular dynamics and hence play a central role in coordinately regulating the growth responses under stress. Recent experimental data unequivocally demonstrated that interactions among various phytohormones are the rule rather than exception in integrating the diverse input signals and readjusting growth as well as acquiring stress tolerance. The presence of multiple and often redundant signaling intermediates for each phytohormone appears to help in such crosstalk. Furthermore, there are several examples of similar developmental changes occurring in response to distinct abiotic stress signals, which can be explained by the crosstalk in phytohormone signaling. Therefore, in this brief review, we have highlighted the major phytohormone crosstalks with a focus on the response of plants to abiotic stresses. The recent findings have made it increasingly apparent that such crosstalk will also explain the extreme pleiotropic responses elicited by various phytohormones. Indeed, it would not be presumptuous to expect that in the coming years this paradigm will take a central role in explaining developmental regulation.